SYNTHESIS AND CHARACTERIZATION OF Nd-CeO2 NANOPARTICLES USING A SIMPLE HEATING METHOD FOR SOLID OXIDE FUEL CELLs (SOFCs) ELECTROLYTE - Sriyanti (NIM 202 05 007), Ida
Abstract : Nd-CeO2 nanoparticles have been synthesized with a simple heating method. The microstructure and morphology of material were characterized by a Scanning Electron Microscopy (SEM), and the conductivity of the material was measured by an AC Impedance Spectroscopy. At room temperature we obtain a sample prepared at 9% at/at. Nd have the highest conductivity of 1.47 x10 -4. Scm -1. This conductivity surpass the value reported by Anefleous for Nd-CeO2 (NDC) material prepared by different method. The size of crystallites was around 49 nm estimated from the width of XRD peak using a warren-scherrer formula. This result proves that a simple heating method is the promising for synthesizing electrolyte materials for Solid Oxide Fuel Cells (SOFCs).